Global metabolic analyses of acinetobacter baumannii - Mahamad Maifiah, Mohd Hafidz; Velkov, Tony; Creek, Darren J.; Li, Jian (Humana Press, 2019)
Acinetobacter baumannii is rapidly emerging as a multidrug-resistant pathogen responsible for nosocomial infections including pneumonia, bacteremia, wound infections, urinary tract infections, and meningitis. Metabolomics provides a powerful tool to gain a system-wide snapshot of cellular biochemical networks under defined conditions and has been increasingly applied to bacterial physiology and drug discovery. Here we describe an optimized sample preparation method for untargeted metabolomics studies in A. baumannii. Our method provides a significant recovery of intracellular metabolites to demonstrate substantial differences in global metabolic profiles among A. baumannii strains.